Performance Investigation of Air Velocity Effects on PV Modules under Controlled Conditions - Muzaffar Ali; Muhammad Hasan Iqbal; Nadeem Ahmed Sheikh; Hafiz M. Ali; M. Shehryar Manzoor; Muhammad Mahabat Khan; Khairul Fikri Tamrin (International Journal of Photoenergy)
Junction temperature of PV modules is one of the key parameters on which the performance of PV modules depends. In the present work, an experimental investigation was carried out to analyze the effects of air velocity on the performance of two PV modules, that is, monocrystalline silicon and polycrystalline silicon under the controlled conditions of a wind tunnel in the presence of an artificial solar simulator. The parameters investigated include the surface temperature variation, power output, and efficiency of PV modules under varying air velocity from near zero (indoor lab. conditions) to 15 m/s. Additionally, the results were also determined at two different module angular positions: at 0° angle, that is, parallel to air direction and at 10° angle with the direction of coming air to consider the effects of tilt angles. Afterwards, the thermal analysis of the modules was performed using Ansys-Fluent in which junction temperature and heat flux of modules were determined by applying appropriate boundary conditions, such as air velocity, heat flux, and solar radiation. Finally, the numerical results are compared with the experiment in terms of junction temperatures of modules and good agreement was found. Additionally, the results showed that the maximum module temperature drops by 17.2°C and the module efficiency and power output increased from 10 to 12% with increasing air velocity.